Factors associated with men's participation in postpartum family planning: a study of Kiswa Health Centre III, Kampala, Uganda - Kizito Omona; Rose Mary Mahoro (Taylor & Francis Group, 2023)
Low uptake of family planning among women is predominantly attributed to low participation of men in postpartum family planning. In order to improve maternal health, strengthening male participation in family planning is an important public health initiative. This study aimed to assess factors associated with participation of men in postpartum care at Kiswa Health Centre III, Nakawa division, Kampala. An analytical cross-sectional study design involving collection of quantitative data was used. Systematic random sampling was used to select study participants. Data was collected using semi-structured questionnaires. Data entry and cleaning was performed using EpiData version 12 and analysed using Stata version 14. 80.0% of respondents participated in postpartum family planning. Approval of family planning use, knowledge on family planning and information source were significantly associated with male involvement in postpartum family planning. Respondents who approved family planning use at home were 15.5 times more likely to get involved in family planning services as compared to those who didn't approve family planning. Conclusively, there was a generally high level of male involvement in postpartum family planning in comparison with the national levels. Approval of family planning at home increased the likelihood of men's participation in family planning.IMPACT STATEMENT What is already known on this subject? Evidence has it that short birth intervals of less than 15 months have been found to be associated with adverse pregnancy outcomes including induced abortions, miscarriages, preterm births, neonatal and child mortalities, still births and maternal depletion syndrome. In Africa, generally, low family uptake among women is also attributed to low men participation in postpartum family planning. What do the results of this study add? Approval of family planning use, knowledge on family planning and information source were associated with male involvement in postpartum family planning. Respondents who approved family planning use at home were 15.5 times more likely to get involved in postpartum family planning services as compared to those who didn't approve family planning. What are the implications of these findings for clinical practice and/or further research? In this study, the involvement of men was relatively high, but more studies are needed in other locations to compare with this finding. Otherwise, consolidation of such high involvement is highly needed, as this can be a starting point for further improvement.